Policing the coronavirus pandemic: Nigeria police senior officers’ views on preparedness, response, legitimacy and post-COVID policing - Aborisade, Richard A. (International journal of police science & management, 2022)
In the wake of pandemic policing occasioned by COVID-19, Nigeria police have been facing challenges of a lack of legitimacy, together with what is termed the militarization of police operations. This has impacted considerably on police–community relations. Meanwhile, early reports on the police response to the pandemic indicated high levels of lockdown violation, despite adoption of a militarized option in the enforcement of restriction orders. In reviewing one of the first police interventions on a public health crisis in Nigeria, a qualitative study was conducted among top-ranking police officers who supervised the enforcement of lockdown and other COVID-19 measures. Sixteen interviews were conducted and a thematic analysis of the narratives was carried out. Police unpreparedness for public health interventions, and public resistance to the use of repressive, force-led styles of policing were identified as major impediments to positive pandemic policing. Therefore, police officers are advised to ensure the application of procedurally just practices in their interactions with the public.